Avaliação da qualidade de alimentos biofortificados produzidos em sistemas agroecológicos do trópico úmido - Silva, Aline Gomes de Moura e [UNESP] (2016)
No-tillage alley cropping is a form of sustainable agriculture that improves soil quality of the humid tropics. The aim of this study was to evaluate the influence of the alley cropping system in the productivity and nutritional quality of biofortified maize and cassava. The highquality protein maize (QPM) BR 473 was grown in Chapadinha (MA). The combinations of legumes were: GA (Gliricidia + Acacia), GS (Gliricidia + Sombreiro), LA (Leucena + Acacia), LS (Leucena + Sombreiro) and the bare soil, with or without addition of 80-80 kg/ha of potassium chloride and urea. The analysis were: 100-grain weight (g), grain/ear, weight of ear, grain yield, proximate composition, mineral content, carotenoids, fatty acid profile and tocopherols. The planting with legume residues and addition of potassium chloride and urea increased corn yield. Regarding protein, urea had greater influence than residues. The combinations of trees without fertilization with urea and potassium chloride had the highest levels of tocopherols. The BRS Dourada cassava was grown in São Luís (MA). The combinations of legumes were: GA (Gliricidia + Acacia), GS (Gliricidia + Sombreiro), LA (Leucena + Acacia), LS (Leucena + Sombreiro), GL (Gliricidia + Leucena) and the bare soil, with or without addition of 100 kg/ha of urea. The analysis were: shoot production, number of roots/plant, root weight, root production, proximate composition, starch, minerals, cooking time, carotenoids profile and pro-vitamin A contents. The yield was greater in GL. The addition of urea to the soil increased the protein and starch contents. For pro-vitamin A, the GS with ureia stood out with 12.4 RAE (Retinol Activity Equivalent) /100 g. The choice of combination of pulses is related to the crop to be planted and the desired quality attribute. The cropping system in alleys was able to increase the production of corn and biofortified cassava and to influence differently each nutrient.